PENGARUH STRUKTUR MODAL TERHADAP KUALITAS LABA DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL INTERVENING - DARA NURLINA, NILA, PUJIONO (Jurnal Akuntansi AKUNESA, 2017)
This study aims to examine the influence between the capital structure to the earnings quality, in addition this study also test the corporate governance as a mediation variable. The type of this research is quantitative using secondary data of indonesian institute for corporate governance with sample annual reports and financial reports of the company. Data were analyzed using descriptive statistical test and Structural Equation Modeling (SEM) analysis by WarpPLS 5.0. The result of this study shows that capital structure not effect on earnings quality but corporate governance can mediate the relationship between capital structure to earnings quality.